EFFECTIVENESS APPLICATION IDENTITY DIGITAL POPULATION (IKD) IN PUBLIC ADMINISTRATION SERVICES IN SIDOARJO REGENCY - Ulhaq, Naufal Alwan Dhiya; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study evaluates the effectiveness of implementing the Digital Population Identity (IKD) in improving the quality of public administrative services in Sidoarjo Regency as part of the government’s digital transformation agenda. Method: A qualitative descriptive approach was adopted, employing interviews, observations, and documentation, with data analyzed using the interactive model of Miles and Huberman to capture comprehensive insights. Results: Findings show that although IKD has been launched across all sub-districts, the activation rate remains relatively low at 13.55% of the total ID-obligated population. Using Budiani’s (2007) effectiveness indicators—program target, socialization, implementation, and evaluation—the study highlights that IKD implementation has yet to reach optimal effectiveness, especially in regions with limited digital infrastructure and low technological literacy. While outreach initiatives such as mobile services and community-based programs have been introduced, they have not sufficiently engaged all community groups. Novelty: This research provides a critical evaluation of IKD as a strategic innovation in population administration, offering new insights into the challenges of digital inclusion and underscoring the importance of equitable access, infrastructure development, and active community involvement for the sustainable success of e-government initiatives.